TREATMENT OF HYPOXIC ISCHEMIC ENCEPHALOPATHY BY APPLYING OF THERAPEUTIC HYPOTHERMIA AT CAMAU OBSTETRICS-PEDIATRIC HOSPITAL FROM 2017 TO 2022 (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate treatment results of neonatal hypoxic ischemic encephalopathy (HIE)by applying of therapeutic hypothermia at Camau Obstetrics and Pediatrics Hospital from 2017 to2022.Method: Cross sectional. 23 HIE newborns were indicated for treatment by therapeutichypothermia at Camau Obstetrics and Pediatrics Hospital from 2017 to 2022.Results: In 23 HIE newborn, male accounted for 78.3%, severe HIE accounted for 48.8%, theaverage age at onset of therapeutic hypothermia was 165.0 ± 88.3 minutes; during procedure56.5% of newborn had convulsions; 26.1% had PH < 7.2; 13.0% had heart rate less 100 beats permin, hyperglycemia requiring insulin-therapy; 8.7% had coagulation disorders, platelets less100,000 per microliter. The mortality rate accounted for 17.4%; Infants with psychomotorretardation recorded at 12 months old were 20.0%; at 18 months old were 16.7%.Conclusion: Hypothermia is significant in the treatment of moderate-severe HIE, contributingto the reduction of mortality and cerebral sequelae.
Keywords: Sơ sinh, bệnh não do thiếu oxy – thiếu máu cục bộ.